Análise comparativa da atividade muscular do flexor superficial dos dedos e força de preensão palmar em atividades laborativas de uma indústria - Rodrigues, Daniel Érico [UNESP] (2014)
This study aimed to develop a device capable of measuring handgrip strength dynamically and verification of operation and adaptability of this device, through a comparative study of strength and muscle activity through electromyography Flexor Superficial fingers in healthy subjects in a work activity of bolting in a automotive company. For this study devised a Device for Measuring Force Gripping Palmar containing gages to evaluate muscle grip strength from playing movements stapling. The study included seven male subjects, aged 20 to 30 years, body mass index between 55 and 80 kg (77.39 ± 13.46 kg) and height between 1.65 and 1.75 m (1.71 ± 0.03 m), healthy with no history of orthopedic disease or any type of injury in the musculoskeletal system. Three collections were performed simulating the motion stitching. Through comparative analysis of the data, no statistical difference between intrasubjectives forces hold and RMS in each collection was observed. It is concluded that the device has built and tested possibilities of quantitative measurement of parameters and the new ergonomic and biomechanical studies can be directed